2017
DOI: 10.1270/jsbbs.16145
|View full text |Cite
|
Sign up to set email alerts
|

Review of major sweetpotato pests in Japan, with information on resistance breeding programs

Abstract: Sweetpotato (Ipomoeae batatas (L.) Lam.) is an important food crop affected by several pests throughout the world, especially in tropical, subtropical, and temperate regions. Although Japan is relatively free from many serious sweetpotato pests, some pests, especially soil-borne pathogens, viruses, and insects such as plant-parasitic nematodes and weevils, cause severe damage in Japan. In this review, we describe the current status and management options for sweetpotato pests and diseases in Japan and review r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
0
17
0
1
Order By: Relevance
“…However, there are few sweet potato cultivars resistant to sweet potato virus disease in the field, especially in East Africa where there is a great demand for virus‐resistant sweet potatoes for subsistence farming. Additionally, resistance observed under experimental conditions may not be reproducible in the field (Okada et al , 2017). It has been documented that CSR3 of SPCSV targets the host plant's RNAi system to cripple the antiviral defence system and increase sweet potato sensitivity to other RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few sweet potato cultivars resistant to sweet potato virus disease in the field, especially in East Africa where there is a great demand for virus‐resistant sweet potatoes for subsistence farming. Additionally, resistance observed under experimental conditions may not be reproducible in the field (Okada et al , 2017). It has been documented that CSR3 of SPCSV targets the host plant's RNAi system to cripple the antiviral defence system and increase sweet potato sensitivity to other RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…These species are almost morphologically indistinguishable and phylogenetically very close (De Beer et al 2014; Kroon et al 2012; Martin et al 2014), but they were reported on very different hosts: P. lateralis attacks Chamaecyparis spp. and other Cupressaceae (Hansen et al 2000; Robin et al 2011), and C. fimbriata is the agent of sweet potato black rot (Okada et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the reasons why the virus is widely distributed in most regions of the country. In addition, movement of the infected storage tubers could also introduce viruses within the small holder farms, as storage roots have been reported to spread the viruses through vegetative propagation (Okada et al, 2017). Coat protein genes have been used in taxonomy of begomoviruses (Padidam et al, 1999) with the nucleotide and amino acid cutoff score of <89 and <90% respectively.…”
Section: Discussionmentioning
confidence: 99%